Nuclear mechano-confinement induces geometry-dependent HP1α condensate alterations - Oda Hovet; Negar Nahali; Andrea Halaburkova; Linda Hofstad Haugen; Jonas Paulsen; Cinzia Progida (Communications Biology)
Abstract Cells sense external physical cues through complex processes involving signaling pathways, cytoskeletal dynamics, and transcriptional regulation to coordinate a cellular response. A key emerging principle underlying such mechanoresponses is the interplay between nuclear morphology, chromatin organization, and the dynamic behavior of nuclear bodies such as HP1α condensates. Here, applying Airyscan super-resolution live cell imaging, we report a hitherto undescribed level of mechanoresponse triggered by cell confinement below their resting nuclear diameter, which elicits changes in the number, size and dynamics of HP1α nuclear condensates. Utilizing biophysical polymer models, we observe radial redistribution of HP1α condensates within the nucleus, influenced by changes in nuclear geometry. These insights shed new light on the complex relationship between external forces and changes in nuclear shape and chromatin organization in cell mechanoreception.